The Impact of Applying Zero-Based Budgeting on the Quality of Internal Control in Economic Units: An Applied Study on Iraqi Banks - Fadhel Abed; Shehlaa Annon; Laith Khaghaany (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2026)
This study examines the impact of applying Zero-Based Budgeting on the quality of internal control in economic units, with an applied focus on Iraqi banks The research aims to determine whether adopting Zero-Based Budgeting contributes to enhancing efficiency transparency, and accountability within internal control systems The study is based on the premise that traditional budgeting methods often rely on incremental adjustments which may overlook inefficiencies, whereas Zero-Based Budgeting requires justification of all expenses from a zero base, thereby strengthening oversight and resource allocation. To achieve the objectives of the study a descriptive analytical approach was adopted supported by an applied field study conducted on a sample of employees working in Iraqi banks Data were collected using a structured questionnaire designed to measure the degree of Zero-Based Budgeting implementation and its influence on internal control components including control environment risk assessment control activities information and communication, and monitoring Statistical tools were employed to analyze the data and test the study hypotheses. The results indicated a statistically significant positive relationship between the application of Zero-Based Budgeting and the improvement of internal control quality The findings showed that Zero-Based Budgeting enhances financial discipline, reduces unnecessary expenditures supports better decision making and improves monitoring procedures. Additionally the application of ZBB was found to strengthen risk assessment practices and increase the effectiveness of control activities within Iraqi banks. The study concludes that adopting Zero-Based Budgeting plays an important role in improving internal control quality in economic units It recommends that Iraqi banks expand the use of Zero-Based Budgeting provide training programs for employees and integrate modern technological tools to support budgeting and control processes These steps are expected to enhance financial performance and strengthen governance frameworks within the banking sector.